Transcription analysis of virulent strains of Mycobacterium tuberculosis - Ambler, Jon Mitchell (Department of Integrative Biomedical Sciences, 2018)
Background: Despite the development of new drugs and success of social programs, tuberculosis remains a leading cause of mortality. This burden falls disproportionately on developing countries where the high burden of HIV has a potentiating e↵ect, but may soon return to areas where it was previously brought under control as resistant strains continue to emerge. In the Western Cape, two closely related strains of the Beijing family have been isolated that provide an opportunity to study virulence in a system with relatively little noise. The aim of this project was to identify the cause of the altered virulence displayed between the two strains, and describe how the di↵erences between the two genomes contributed to the phenotypic di↵erences. Results: GenGraph allows for the creation of graph genomes, and facilitated the creation of a pan-transcriptome that allowed for the mapping of gene annotations between isolates. This allowed for the mapping of reads to a more suitable Beijing family reference while interpreting the results with annotations from the H37Rv reference. We generated expression and target profiles for the known sRNA, and identified a large number of novel sRNA. Transcriptomic data from 4 di↵erent growth conditions was integrated with this sRNA data as well as variant data using the Cell pipeline. From this data we identified multiple sets of genes linked to copper sensing in MTB, including the di↵erentially expressed MoCo operon. Increasing evidence that macrophages use copper to poison bacteria trapped in their phagosomes provides the link to virulence and pathogenicity. Conclusions: Through the integration of data from multiple data types we were able to elucidate the most probable cause of the altered virulence found between the two isolates in this study. We developed reusable tools and pipelines, and noted a large number of undescribed sRNA expressed in these isolates. The identification of the copper response as a chief contributor to the phenotype increases both our understanding of the isolates, and the role of the element in infection. These results will be key in guiding further investigation of the variant linked genes to identify those linked to copper homeostasis or response.